ВОПРОСЫ ИСПОЛЬЗОВАНИЯ ВОДНЫХ РЕСУРСОВ В УЗБЕКИСТАНЕ И СТРАНАХ ЦЕНТРАЛЬНОЙ АЗИИ - Раджапов, М.Я. (SCIENCE and SOCIETY, 2025)
This article examines the ecological situation in the Central Asian region and emphasizes the importance of environmental problems. An analytical review of the use of water resources in Uzbekistan and neighboring countries was conducted, and it was noted that the formation of rivers in the region occurs mainly in the mountainous part, where precipitation is used for irrigation and other purposes due to evaporation. Annual decrease in water resources in the republic, the region belongs to the group of countries with high water stress and its (water) shortage.